The effect of Allium sativum and Capsicum spp. Watery extracts on the Entamoeba histolytica in vitro. (Baghdad Science Journal, 2025)
In vitro tests have been carried out to find out the efficacy of watery extracts of garlic Allium sativum and hot pepper Capsicum spp. against the trophozoites of Entamoeba histolytica cultivated in liver infusion agar media at 37 c .The doses of ( 0.01, 0.05 ,0.1, 0.5, 1 ml )of garlic and hot pepper watery extracts were added to certain number of E. histolotica trophozoits for exposure time of 24 hrs., the mortality percentage of trophozoites treated with garlic extract were ( 14.82 %, 31.05% ,46.16% , 64.29% , 92.7%) respectively , these percentages were very close to that obtained from the treatment with the hot peper extract which were (17.86%, 32% , 44% ,66.67% ,100%) respectively .Generally these results showed that the garlic and hot pepper watery extracts both were effective to eliminate E. histolitica trophozaites ,particularly the doses of (0.5 and 1 ml).The differences in studied plant characters were significant in the case of the first concentration compared with the second one.